2012
DOI: 10.1261/rna.035881.112
|View full text |Cite
|
Sign up to set email alerts
|

Yeast eIF4B binds to the head of the 40S ribosomal subunit and promotes mRNA recruitment through its N-terminal and internal repeat domains

Abstract: Eukaryotic translation initiation factor (eIF)4B stimulates recruitment of mRNA to the 43S ribosomal pre-initiation complex (PIC). Yeast eIF4B (yeIF4B), shown previously to bind single-stranded (ss) RNA, consists of an N-terminal domain (NTD), predicted to be unstructured in solution; an RNA-recognition motif (RRM); an unusual domain comprised of seven imperfect repeats of 26 amino acids; and a C-terminal domain. Although the mechanism of yeIF4B action has remained obscure, most models have suggested central r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
154
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(176 citation statements)
references
References 54 publications
19
154
3
Order By: Relevance
“…Stable eIF4A/eIF4B complexes have been identified in pulldown experiments for the mammalian counterparts only. 18,19 A direct interaction of yeast eIF4A and eIF4B is supported by the observed stimulation of the eIF4A helicase activity by eIF4B 9 and the promotion of the eIF4A-PIC interaction by eIF4B, 16 and by genetic studies, 20 but has not been shown experimentally. In conventional binding experiments (such as size-exclusion chromatography or pull-down experiments) reactants are mixed at concentrations that favor complex formation, but multiple washing steps and the concomitant dilution may allow dissociation of the binding partners.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Stable eIF4A/eIF4B complexes have been identified in pulldown experiments for the mammalian counterparts only. 18,19 A direct interaction of yeast eIF4A and eIF4B is supported by the observed stimulation of the eIF4A helicase activity by eIF4B 9 and the promotion of the eIF4A-PIC interaction by eIF4B, 16 and by genetic studies, 20 but has not been shown experimentally. In conventional binding experiments (such as size-exclusion chromatography or pull-down experiments) reactants are mixed at concentrations that favor complex formation, but multiple washing steps and the concomitant dilution may allow dissociation of the binding partners.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown previously that yeast eIF4B binds to 40S ribosomal subunits, and mediates recruitment of the PIC to the mRNA, possibly through interactions with eIF4A. 16 PIC recruitment depends on the presence of the r1-7 region of eIF4B, and to a lesser extent on the NTD. 16 Human eIF4A and eIF4B form a stable complex.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations